Academic inventions outside the university: investigating patent ownership in the UK - Lawson, Cornelia (Taylor & Francis, 2013)
This paper investigates the ownership of academic patents for a sample of UK academics and challenges the existing definition of the university invention ownership model. The first descriptive results show that 50% of patents are owned by industry, however, 37% of these firm-assigned patents are in fact owned by university spin-offs. We investigate how university policy and funding acquisition impacts industry vs. university ownership, and find that funding from large firms predicts involvement in patenting and, to a lesser extent, firm ownership. University ownership of academic patents is more likely the higher the amount of funding coming from SMEs, and at universities that outsource the filing of patents. Spin-off patents occupy an intermediate position showing strong similarities to both firm and university patents.